Rancang Bangun Miniatur Stasiun Cuaca Untuk Monitoring Curah Hujan, Suhu Dan Kelembaban Udara Area Lokal Menggunakan Berbasis IOT - Refi Amalianti; Abdul Jabbar Lubis; Imran Lubis (SEMINAR NASIONAL TEKNOLOGI INFORMASI & KOMUNIKASI, 2021)
News or news about the weather becomes a common necessity at this time, because many activities depend on weather conditions. Weather news that is commonly used daily is temperature, humidity, and rainfall. In this weather monitoring process utilizing IoT as a concept whose purpose is to expand the benefits of continuously connected internet connectivity, and also users can build their own information network including building their own weather monitoring system that can be used in the desired local area, which is used to observe weather conditions in residential or local areas, Because there is often a difference in weather between one area and another.From these problems came the idea to create a tool "Design Miniature Weather Stations For Monitoring Rainfall, Temperature and Humidity of Local Area Air Using IoT (Internet of Things)" based. This tool utilizes sensors that can detect precipitation, sensors that can detect temperature and humidity and components that can monitor the weather when we are anywhere far away and anytime. In this study the system used arduino uno microcontroller that serves as a device that activates all components, such as hall effect sensor, DHT22 sensor, RTC DS3231, Wemos D1 Mini ESP8266, LCD, I2C, DC Converter LM2596, where this device can connect microcontroller devices such as Arduino Uno with the internet via WiFi hotspots.